2016
DOI: 10.3390/atmos7050068
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Atmospheric Glyoxal Column Densities Retrieved from MAX-DOAS Observations in Pakistan and during MAD-CAT Field Campaign in Mainz, Germany

Abstract: Photolysis of glyoxal (CHOCHO) and other volatile organic compounds (VOC) in the presence of NOx results in tropospheric ozone and secondary organic pollutants formation. Glyoxal, with a relatively short lifetime, plays an important role in VOC formation in the planetary boundary layer. This study presents a comparative analysis of CHOCHO retrieval from mini MAX-DOAS observations at two different monitoring sites in Germany and Pakistan. Firstly, CHOCHO differential slant column densities (DSCDs) were retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…On the other hand, we found that the profiling algorithm for glyoxal was not sensitive enough to layers above 1 km, thus the corresponding VCDs yielded larger uncertainties (and even two months, January and April, without reliable results for the entire column) than the surface mixing ratios. Our retrieved results of glyoxal VCDs are higher (in the order of twice as much) than other reported for urban environments using the DOAS technique (Sinreich et al, 2007) although there is a good agreement with the range reported in Khokhar et al, 2016. Our values fall within the typical range (0.04-4.1 ppbv) reported by the World Health Organization (Kielhorn et al, 2004) for urban environments. In addition, the lack of a strong temporal evolution compares to that observed for HCHO at the same time of day.…”
Section: Glyoxal Profilessupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, we found that the profiling algorithm for glyoxal was not sensitive enough to layers above 1 km, thus the corresponding VCDs yielded larger uncertainties (and even two months, January and April, without reliable results for the entire column) than the surface mixing ratios. Our retrieved results of glyoxal VCDs are higher (in the order of twice as much) than other reported for urban environments using the DOAS technique (Sinreich et al, 2007) although there is a good agreement with the range reported in Khokhar et al, 2016. Our values fall within the typical range (0.04-4.1 ppbv) reported by the World Health Organization (Kielhorn et al, 2004) for urban environments. In addition, the lack of a strong temporal evolution compares to that observed for HCHO at the same time of day.…”
Section: Glyoxal Profilessupporting
confidence: 87%
“…Finally, the best configuration found (with the lowest residual RMS and a good spectral fitting) was the following: wavelength range of 425-457 nm with a gap between 442 and 449 nm. There are some discrepancies about the wavelength region used in the glyoxal DOAS analysis: Sinreich et al, 2007 used a 133 wavelength between 420 and 460 nm; Coburn et al, 2014 applied a wavelength range of 433-460 nm, and the 434-460 nm window was used in Khokhar et al, 2016. For HCHO, the wavelength range used in this study follows that of previous reports: Heckel et al, 2005 applied a fitting window between 335 and 357 nm, 336.5-359 nm was used in Pinardi et al, 2013;336-358 nm in Vigouroux et al, 2009 and 336-359…”
Section: Methodsmentioning
confidence: 99%
“…The combustion processes in vehicles and industry are the major source of air pollutants such as sulfur dioxide (SO 2 -WHO, 2005;Johansson et al, 2008;Kalabokas et al, 2012;Khattak et al, 2014), carbon monoxide (CO -WHO, 2005;Seinfeld and Pandis, 2012), nitrogen oxides (NO x -WHO, 2005;Frins et al, 2012;Shabbir et al, 2015;Khokhar et al, 2015a) and particulate matter (PM - Khokhar et al, 2016a and references therein) in the air. Globally, nitrogen oxides (NO x = NO + NO 2 ) are released through combustion of fossil fuel, biomass burning, lightning and microbiological processes in soil (Lee et al, 1997;Boersma et al, 2005;HSDB, 2007).…”
Section: Introductionmentioning
confidence: 99%